(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
From the trend analysis as well as the regressionanalysis it is now clear that there is positive relationship between totalprimary energy consumption to GDP, population, and per capita energy consumption,however a negative relationship do exist between the energy use and theproduction of the energy resources in case of India. From the study one cansummarize that total primary energy use is one of the key components of theGDP. Population is an important factor for the total primary energy consumptionand one of the major contributors for the demand of more energy resources. Percapita energy consumption in the economy has a positive relationship with thetotal energy use. Hence it is one of the important factors of the total energyconsumption. As evidence from the developing countries more the nation developseconomically, the demand for energy resources also increases. Our findings alsosuggests in the same way, as increase in GDP, Population, Per capitaconsumption leads to more demand of energy resources.